Inhibition of CD44 intracellular domain production suppresses bovine articular chondrocyte de-differentiation induced by excessive mechanical stress loading - Sobue, Yasumori; Takahashi, Nobunori; Ohashi, Yoshifumi; Suzuki, Mochihito; Nishiume, Tsuyoshi; Kobayakawa, Tomonori; Terabe, Kenya; Knudson, Warren; Knudson, Cheryl; Ishiguro, Naoki; Kojima, Toshihisa (My University, 2019)
CD44 fragmentation is enhanced in chondrocytes of osteoarthritis (OA) patients. We hypothesized that mechanical stress-induced enhancement of CD44-intracellular domain (CD44-ICD) production plays an important role in the de-differentiation of chondrocytes and OA. This study aimed to assess the relationship between CD44-ICD and chondrocyte gene expression. Monolayer cultured primary bovine articular chondrocytes (BACs) were subjected to cyclic tensile strain (CTS) loading. ADAM10 inhibitor (GI254023X) and γ-secretase inhibitor (DAPT) were used to inhibit CD44 cleavage. In overexpression experiments, BACs were electroporated with a plasmid encoding CD44-ICD. CTS loading increased the expression of ADAM10 and subsequent CD44 cleavage, while decreasing the expression of SOX9, aggrecan, and type 2 collagen (COL2). Overexpression of CD44-ICD also resulted in decreased expression of these chondrocyte genes. Both GI254023X and DAPT reduced the production of CD44-ICD upon CTS loading, and significantly rescued the reduction of SOX9 expression by CTS loading. Chemical inhibition of CD44-ICD production also rescued aggrecan and COL2 expression following CTS loading. Our findings suggest that CD44-ICD is closely associated with the de-differentiation of chondrocytes. Excessive mechanical stress loading promoted the de-differentiation of BACs by enhancing CD44 cleavage and CD44-ICD production. Suppression of CD44 cleavage has potential as a novel treatment strategy for OA.